1987
DOI: 10.1002/1097-0142(19870601)59:11<1860::aid-cncr2820591103>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy for advanced head and neck cancer with allopurinol-modulated high dose 5-fluorouracil and cisplatin a phase I-II study

Abstract: The combination of cisplatin (100 mg/m2) and 5-fluorouracil (5-FU) by continuous infusion (1 g/m2/day for 5 days) has been reported to produce a high response rate as neoadjuvant therapy for advanced squamous cell head and neck cancer. We sought to improve the response rate by increasing the dose of 5-FU to 1.5 g/m2/day and 2.0 g/m2/day with allopurinol modulation to reduce toxicity. The overall response rate in the 30 patients who received three courses of chemotherapy was 100% with a 50% complete response (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although 5-FU is one of the anticancer agents employed as a single agent for advanced gastric cancers, response rates with single agents such as 5-FU, mitomycin, doxorubicin, epirubicin, and cisplatin are reported to be 20%-30% [3]. 5-FU combined with cisplatin has been used clinically to increase efficacy, and recent clinical data have shown the synergistic effects of cisplatin with 5-FU in patients with gastrointestinal cancers [4][5][6] and other types of cancers, including head and neck cancers [2,[7][8][9]. Although the mechanism of the synergistic effect has been debated for years [10,11], it has been demonstrated, in vitro, that cisplatin works as a biomodulator of the effect of 5-FU by increasing the availability of reduced folate, which may result in an increase in thymidylate synthase (TS) inhibition [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although 5-FU is one of the anticancer agents employed as a single agent for advanced gastric cancers, response rates with single agents such as 5-FU, mitomycin, doxorubicin, epirubicin, and cisplatin are reported to be 20%-30% [3]. 5-FU combined with cisplatin has been used clinically to increase efficacy, and recent clinical data have shown the synergistic effects of cisplatin with 5-FU in patients with gastrointestinal cancers [4][5][6] and other types of cancers, including head and neck cancers [2,[7][8][9]. Although the mechanism of the synergistic effect has been debated for years [10,11], it has been demonstrated, in vitro, that cisplatin works as a biomodulator of the effect of 5-FU by increasing the availability of reduced folate, which may result in an increase in thymidylate synthase (TS) inhibition [10].…”
Section: Introductionmentioning
confidence: 99%
“…reported that the mucosal injury induced by radiochemotherapy is comprised of the following 5 processes1: initiation by production of reactive oxygen species,2 nuclear factor‐κB (NF‐κB) activation followed by induction of inflammatory cytokines such as TNF‐α, IL‐1β and IL‐6,3 TNF‐α‐mediated production of ceramide and caspase activation that leads to cell apoptosis,4 ulceration with inflammation and5 healing. On the basis of these assumptions, a number of compounds have been clinically tested for prevention of oral mucositis in the therapy of head and neck cancer, including antioxidants such as amifostine,7–10 vitamine E,11 melatonin12 and allopurinol,13 mucosal protectant such as sucralfate,14 benzydamine, a nonsteroidal antiinflammatory drug with local anesthetic action,15, 16 and prostaglandin E 1 analog 17. However, none of them has been confirmed to reveal consistent protective action against radiation‐ or radiochemotherapy‐induced oral mucositis.…”
mentioning
confidence: 99%
“…5-fl uorouracil metabolises quickly in the body (in liver) to dihydro-5-fl uorouracil; approximately 20 % is excreted in urine in an unchanged form (the half-time is 10-15 minutes). The swift decline in plasma concentration after single administration explains why continual infusion manifests more marked antitumour effi ciency 8,10,12,13 .…”
Section: Pyrimidine Analogues (Uracil Analogues Fl Uroinated Pyrimidmentioning
confidence: 99%